LINEARIZATION OF MULTI-LIPSCHITZ MAPS ON BANACH SPACES - Загороднюк, Андрій Васильович; Дубей, Марія Володимирівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We consider Lipschitz and multi-Lipschitz maps and we carry out the process of linearization of multi-Lipschitz maps.